Wednesday

April 23, 2014

April 23, 2014

Posted by **Yoona** on Monday, January 2, 2012 at 1:55pm.

a. Find the absolute maximum and minimum values of f(x)

b. Find the intervals on which f is increasing.

c. Find the x-coordinate of each point of inflection of the graph of f.

- calculus -
**Yoona**, Monday, January 2, 2012 at 1:56pmsorry for the double post

- calculus -
**Reiny**, Monday, January 2, 2012 at 5:19pmf(x) = e^x (cosx)

f'(x) = e^x(-sinx) + e^x(cosx)

= e^x(cosx - sinx) = 0 for max/min values of f(x)

so e^x = 0 , no solution

or

cosx - sinx = 0

sinx= cosx

sinx/cosx = 1

tanx = 1

x = π/4 or 5π/4

f(0) = e^0(cos0) = 1

f(2π) = e^(2π)(1) = e^(2π) = appr. 535.5

f(π/4) = e^(π/4) (√2/2) = appr. 1.55

f(5π/4) = e^(5π/4) cos 5π/4 = appr. -35.9

take it from there

b) the function is increasing when f'(x) > 0

e^x(cosx - sinx) > 0

since e^x > 0 for all x

this results in cosx - sinx >0

-sinx > -cosx

sinx/cosx < 1

tanx < 1

So for the domain from 0 to 2π

tanx < 1 for

0 < x < π/4 OR π/2 < x < 5π/4 OR 3π/2 < x < 2π

( I looked at the tangent curve for these)

c) take the derivative of f'(x)

f''(x) = e^x(-cosx) + e^x(-sinx) + e^x(-sinx) + e^x(cosx)

= -2e^x sinx

= 0 for pts of inflection

then sinx = 0

x = 0 , π, 2π

**Related Questions**

calculus - 2. Consider the function f defined by f(x)=(e^X)cosx with domain[0,...

calculus help please - Consider the function f(x)=2x+9x^–1.? For this function ...

CALCULUs - For all x in the interval [-11,13] the function f is defined by x^3(x...

Math, Calculus - Find the derivative of the function. y= xcosx - sinx What's the...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

math-calc - Consider the function f(x)= (2x+8)/(6x+3). For this function there ...

calculus - For x including [–15, 13] the function f is defined by f(x)=x^7(x+4)^...

Calculus - A function is implicitly defined by x^2 - 4y^2 = 9 Find the equation ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...